MEETING ESP NEEDS OF NURSING STUDENTS: PERSPECTIVES FROM STUDENTS AND PROFESSIONAL - Agustina, Noni; Susanto, Ratnawati; Asmirajanti, Mira; Astrada, Adam; Vionalita, Gisely (TELL - US JOURNAL, 2025)
The nursing profession in Indonesia is rapidly developing, with an increasing demand for skilled nurses who can provide high-quality patient care. As the healthcare industry becomes increasingly globalized, the ability to communicate effectively in English is becoming an essential skill for nurses. However, existing English language teaching materials for nursing do not adequately prepare nursing students and practicing nurses to face the challenges they will encounter in the global healthcare environment. To address this gap, it is necessary to develop new teaching materials specifically tailored to the needs of Indonesian nurses. Therefore, it is crucial to explore the English language needs for professional nurses in developing future English for nursing curricula and teaching materials that align with the demands of the workforce. This research has high urgency and novelty because it involves nursing students at University X in West Jakarta, Indonesia, and professional nurses who work using English as a medium, thereby connecting global needs with campus learning. The involvement of these professional nurses contributes to authentic English language input in the nursing context. Qualitative research using semi-structured interviews and questionnaires with open-ended questions will be used to collect data. The research results have implications for the development of teaching materials, curricula, and campus learning.